Regioselective acylation of flavonoids catalyzed by lipase in low toxicity media - Kontogianni, A; Skouridou, V; Sereti, V; Stamatis, H; Kolisis, FN (WILEY-V C H VERLAG GMBH, 2001)
Flavonoid fatty esters were prepared by acylation of flavonoids (rutin and naringin) by fatty acids (C8, C10, C12), catalyzed by immobilized lipase from Candida antarctica in various solvent systems. The reaction parameters affecting the conversion of the enzymatic process, such as the nature of the organic solvent and acyl donor used, the water activity (a(w)) of the system, as well as the acyl donor concentration have been investigated. At optimum reaction conditions, the conversion of flavonoids was 50-60% in tert-butanol at a(w) less than 0.11. In all cases studied, only flavonoid monoester was identified, which indicates that this lipase-catalyzed esterification is regioselective.